PERANAN LETNAN MUDA M. WASMAD RADS DALAM MEMPERTAHANKAN KEMERDEKAAN DI RENGAT TAHUN 1945-1949 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Young Lieutenant M. Wasmad Rads was one of the figures who fought for the defense of the independence of the Republic of Indonesia in Rengat in 1945-1949. Young Lieutenant M. Wasmad Rads was born in Sekip, Rengat, June 26, 1926 to parents named Mujoyo and Paisah. Young Lieutenant M. Wasmad Rads is the second of five children. The research objectives (1) were to define the curriculum vitae of the young Lieutenant M. Wasmad Rads (2) to determine the role of M. Wasmad Rads in defending independence in Rengat in 1945-1949 (3) to to determine the end of the fight of the young Lieutenant M. Wasmad Rads. The method used in this research is to use the historical method in the steps heuristics, verification, interpretation, and historiography. Young Lieutenant M. Wasmad Rads's role in defending independence in Rengat began with the SINAR organization he led. Young Lieutenant M. Wasmad Rads invited his friends to fight against the invaders. And the young Lieutenant M. Wasmad Rads was the person who took the initiative to raise the red and white flag for the first time in Rengat, and he was one of the special committees that carried out the flag ceremony in Rengat, as well as Deputy Lieutenant M. Wasmad Rads reading the proclamation and signing the letter of power transfer. from Japanese hands to Indonesian hands at the first flag ceremony in Rengat, then young Lieutenant M. Wasmad Rads was also involved in Military Aggression II in Rengat.Key Words: M. Wasmad Rads, Struggle,Maintain, Independence